Tax planning by multinational firms Firm-level evidence from a cross-country database - Johansson, Åsa (OECD Publishing, 2017)
This paper exploits firm-level data from the ORBIS database to assess international tax planning by multinational enterprises (MNEs). Profit shifting to lower-tax rate countries is measured by comparing the profitability of MNE entities having different links to countries with different tax rates and thus different profit shifting opportunities. The paper also considers other aspects of tax planning that have been less documented in the empirical literature, such as the exploitation of mismatches between tax systems and preferential tax regimes, by comparing how profits reported by MNE entities are taxed relative to non-multinational entities with similar characteristics. The analysis builds on available unconsolidated financial account data, which, despite its limitations, is considered as the best existing cross-country firm-level data. Results are based on a very large sample of firms (1.2 million observations of MNE accounts) in 46 OECD and G20 countries and a sophisticated procedure to identify MNE groups. They provide robust evidence that MNEs shift profits to lower-tax rate countries and that large MNEs also exploit mismatches between tax systems and preferential tax treatment to reduce their tax burden. Overall, the estimated net tax revenue loss ranges from 4% to 10% of global corporate tax revenues. The empirical analysis also shows that strong "anti-avoidance" rules against tax planning are associated with reduced profit shifting, but also higher compliance costs for firms
Keywords: Taxation; Economics